A Literature Review on Scientific Issues in The Implementation of State-Owned Aset Management Policy in Indonesia - Rachmat Alamsyah; Heru Nurasa; Candradewini Candradewini (Eduvest - Journal of Universal Studies, 2025)
The management of Indonesia's State-Owned Assets (SOA), valued at IDR 6,388.18 trillion in 2023, faces challenges due to complex administrative processes, fragmented policy implementation, and limited human resource capacity. This study aims to analyze scientific discussions on SOA management policy implementation, identify research trends, and highlight knowledge gaps for future improvement. A Systematic Literature Review (SLR) method analyzed 139 scientific articles from Google Scholar and Scopus databases (2018–2023). The findings reveal that SOA administration is the most frequently discussed theme, consistently addressed yearly, reflecting its vital role in government financial reporting. However, research on supervision, control, borrowing, lending, and disposal remains scarce. The dominant factors influencing policy implementation are human resources and information systems. This study implies that policymakers need to enhance functional positions in SOA management and improve technological infrastructure. For academics, this review provides a comprehensive overview of SOA management research and offers a basis for further empirical studies focusing on underexplored themes, supporting continuous improvement in public asset governance.